2022
DOI: 10.1101/2022.12.13.520154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First fully-automated AI/ML virtual screening cascade implemented at a drug discovery centre in Africa

Abstract: We present ZairaChem, an artificial intelligence (AI)- and machine learning (ML)-based tool to train small-molecule activity prediction models. ZairaChem is fully automated, requires low computational resources and works across a broad spectrum of datasets, ranging from whole-cell growth inhibition assays to drug metabolism properties. The tool has been implemented end-to-end at the Holistic Drug Discovery and Development (H3D) Centre, the leading integrated drug discovery unit in Africa, at which no prior AI/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…This tool represents a significant advancement in enabling streamlined drug discovery processes, informing compound progression, and facilitating lead identification in resource-limited settings. Through real-world prospective studies, ZairaChem has demonstrated its efficacy in identifying lead-like compounds, showcasing its potential to revolutionize drug discovery efforts [44].…”
Section: Traditional Methods Vs Ai-driven Lead Optimizationmentioning
confidence: 99%
“…This tool represents a significant advancement in enabling streamlined drug discovery processes, informing compound progression, and facilitating lead identification in resource-limited settings. Through real-world prospective studies, ZairaChem has demonstrated its efficacy in identifying lead-like compounds, showcasing its potential to revolutionize drug discovery efforts [44].…”
Section: Traditional Methods Vs Ai-driven Lead Optimizationmentioning
confidence: 99%
“…In conclusion, GPT‐based AI tools have great potential to facilitate the complex, expensive, and time‐consuming drug development process by identifying the most promising drug targets and potential lead compounds (Tiwari et al, 2023; Turon et al, 2023). Improved GPT‐based tools will be coming, and the pharma R&D sector will need to identify and prioritize the optimal modes for using them.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Ligand-based methods often do not require a knowledge of the structural features of a receptor site (Ferreira et al 2015;Vazquez et al 2020). These include quantitative structure-activity relationships (QSAR), ligand-based pharmacophore querying methods, and most recently, artificial intelligence/machine learning (AI/ML) models (Selvaraj et al 2022;Subramanian et al 2022;Namba-Nzanguim et al 2022;Turon et al 2023). Among these methods, the most cite is molecular docking and scoring techniques have been proven to be efficient ways of identifying active compounds from an electronic library of compounds by a what is commonly called virtual screening (Morris & Lim-Wilby 2008;Chen 2015;Lohning et al 2017).…”
Section: Introductionmentioning
confidence: 99%